KUALITAS SITUS WEB, KEPERCAYAAN, KEPUASAN DAN LOYALITAS PEMBELANJA MUDA DI TOKO ONLINE - WIDAYAT; SILVA YUNI ARTIKA (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2019)
This research aims to examine the effect of web quality variables, on online shop customer loyalty, by positioning trust variables and satisfaction as mediation. The population of this study was adolescent. Samples of 100 respondents were selected using accidental sampling. The data from the respondents were collected using questionnaire, then analyzed using Partial Lease Square assisted by SmartPLS software. The results of the analysis show that customer loyalty is not influenced by the quality of the web directly. Satisfaction and trust play a role in mediating the effect of page quality on online store customer loyalty, significantly